2016
DOI: 10.1136/bmjopen-2015-009750
|View full text |Cite
|
Sign up to set email alerts
|

Discovering untapped relationship potential with patients in telehealth: a qualitative interview study

Abstract: Objectives: To explore factors that influence relationship building between telehealth professionals and patients with chronic illness over a distance, from a telehealth professional's perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 28 publications
1
39
0
1
Order By: Relevance
“…Nonetheless, some studies reviewed demonstrated that survivors were able to develop trusting relationships with HCPs via the telehealth medium [30,31,40,49], and other studies of telehealth interventions have demonstrated the capacity for such relationships to develop [69-71]. In addition, cancer survivors found they could more easily raise concerns with their HCP remotely, concerns that they would otherwise feel uncomfortable to discuss in person [40,47].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some studies reviewed demonstrated that survivors were able to develop trusting relationships with HCPs via the telehealth medium [30,31,40,49], and other studies of telehealth interventions have demonstrated the capacity for such relationships to develop [69-71]. In addition, cancer survivors found they could more easily raise concerns with their HCP remotely, concerns that they would otherwise feel uncomfortable to discuss in person [40,47].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a qualitative study led with interviews, it was observed that non-video telehealth technologies fostered the sharing of personal information and a non-judgemental attitude in patients, but each contact between a telehealth professional and a patient required a skilful negotiation of the relationship to engage the patient as an "expert of their own illness". 51 In addition, it has been pointed out recently that HF selfmanagement may be associated with reduced hospital admissions only in a subgroup of patients with HF (i.e. patients under 65 years of age), whereas in other subgroups (patients with moderate or severe depression), involvement in self-management may be even associated with a reduced survival rate.…”
Section: Patient Participationmentioning
confidence: 99%
“…Telerehabilitation consultations also encourage effective communication between patients and clinicians, providing patients with a sense of personalized, undivided focus, and attention (Hinman et al., ; Lawford et al., 2018a, 2018b) which facilitates delivery of person‐centered care. In addition, the anonymity of telephone consultations has been found to encourage the sharing of personal information and development of a non‐judgmental attitude during consultations (Heckemann, Wolf, Ali, Sonntag, & Ekman, ). This counters common misconceptions that telerehabilitation is an “impersonal” mode of service delivery (Kayyali et al., ) and instead suggests that the conversational nature of consultations can facilitate an increased emphasis on behavior change support and exercise adherence.…”
Section: Technology Provides Opportunities For Remotely‐delivered Sermentioning
confidence: 99%